Genetic Diversity and Relationship among Bali Cattle from Several Locations in Indonesia Based on ETH10 Microsatellite Marker - Endang Tri Margawati; Slamet Diah Volkandari; Indriawati Indriawati; Muhamad Ridwan (Jurnal Ilmu Ternak dan Veteriner, 2018)
Bali cattle is one of local beef cattle in Indonesia, up to present its performance indicated an inbreeding occurrence. This study was aimed to analyze the genetic diversity and relationship among Bali cattle from several locations in Indonesia based on ETH10 microsatellite marker. Ninety-four (94) DNA samples (89 Bali cattle; 5 Banteng) were analyzed. The Bali cattle samples were from 6 locations in Indonesia (15 Pulukan; 15 Nusa Penida; 14 Bima West Nusa Tenggara/WNT; 10 Mataram, WNT; 20 Riau; 15 South Borneo). DNA Banteng samples were collected from Prigen Malang of East Java. Microsatellite marker of ETH10 labelled HEX was used for amplification. Alleles were analyzed by using Cervus 3.0.7 and GenAlex 6.5. Result showed that there were five (5) alleles found in ETH10 marker i.e., 209; 213; 215; 217; and 219 bp. Average of observed (Ho) and expected (He) heterozygosity were 0.46±0.05 and 0.60±0.03, respectively. Five (5) out of 6 locations were in breeding occurrence except Bali cattle from Mataram was not inbreeding. The longest genetic relationship was between Bali cattle from Mataram and Riau whereas the closest distance was Bali cattle from South Borneo with Mataram. Banteng was closest to Bali cattle from Nusa Penida and the longest was to Bali cattle from South Borneo. This finding indicates there is inbreeding in Bali cattle, therefore it needs to be concerned in bull rotation and semen distribution for increasing the Bali cattle performance.